Investigation of Defects in Hydrogen-Saturated Titanium by Means of Positron Annihilation Techniques; Defect and Diffusion Forum; Vol. 365 : Diffusion in Solids and Liquids X - Laptev R. S. Roman Sergeevich; Lider A. M. Andrey Markovich; Bordulev Yu. S. Yuri Sergeevich; Kudiyarov V. N. Victor Nikolaevich; Garanin G. V. Georgy Viktorovich; Wang Wei; Kuznetsov P. V. Pavel Viktorovich (2015, 2015)
Title screen